Assessment of immune response to Hepatitis B vaccine by estimation of anti - HBs antibody titer among immunized health care workers - Gitanjali Kailas Badave; Priyanka Puneriya (Tropical Journal of Pathology and Microbiology, 2019)
Background: Hepatitis B vaccination is recommended for all health care workers as they constitute a high-risk group for acquiring blood borne hepatitis B infection. Anti HBs level ≥10 mIU/ml at any time after vaccination is considered as a marker of sustained immunity, which provides protection against infection. Poor sero-protection rates to hepatitis B vaccine are recognized and some individuals do not develop sufficient levels of anti-HBs antibodies. Hence, it is necessary to identify the individuals who are non-protective responders to vaccination. With this background, the present study was undertaken to determine immune response to hepatitis B vaccine amongst the health care workers.Material and Methods: The present cross-sectional study included 200 health care workers in a tertiary teaching hospital, who were immunized with three complete doses of hepatitis B vaccine. Quantitative determination of anti HBs levels was done by ELISA. The effect of gender, age, smoking, body mass index and duration after immunization on antibody levels were analyzed.Results: The association of anti-HBs status and gender was not statistically significant. Increase in age leads to decline of anti-HBs protective responders. Smoking and higher body mass index are significantly associated with less anti HBs titers (<10 mIU/ml).Conclusion: The highest number of protective responders is seen in initial 5 years post vaccination duration and least protective responders are observed in >10 years post vaccination duration, indicating decline in antibody response over a period of time.